2008
DOI: 10.1111/j.1462-2920.2008.01724.x
|View full text |Cite
|
Sign up to set email alerts
|

Denitrifying bacteria anaerobically oxidize methane in the absence of Archaea

Abstract: Recently, a microbial consortium was shown to couple the anaerobic oxidation of methane to denitrification, predominantly in the form of nitrite reduction to dinitrogen gas. This consortium was dominated by bacteria of an as yet uncharacterized division and archaea of the order Methanosarcinales. The present manuscript reports on the upscaling of the enrichment culture, and addresses the role of the archaea in methane oxidation. The key gene of methanotrophic and methanogenic archaea, mcrA, was sequenced. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
290
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 416 publications
(313 citation statements)
references
References 47 publications
17
290
1
4
Order By: Relevance
“…The wide range in growth temperature of anammox bacteria may promote their existence in wetlands. So far, the NC10 bacteria have only been detected in moderate fresh water sediments with temperatures between 10°C and 30°C (Ettwig et al 2008(Ettwig et al , 2009Hu et al 2009). …”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The wide range in growth temperature of anammox bacteria may promote their existence in wetlands. So far, the NC10 bacteria have only been detected in moderate fresh water sediments with temperatures between 10°C and 30°C (Ettwig et al 2008(Ettwig et al , 2009Hu et al 2009). …”
Section: Temperaturementioning
confidence: 99%
“…This discovery and potential contribution of anammox bacteria is important because it may necessitate a re-evaluation of the major fluxes in the global nitrogen budget and regulation of the processes leading to losses of fixed nitrogen. The addition of nitritedependent anaerobic methane oxidation (ANME coupled to denitrification) to the nitrogen cycle is even more recent (Raghoebarsing et al 2006;Ettwig et al 2008). Anoxic sediment from a fresh water canal in The Netherlands was used as an inoculum and supplied with methane, nitrate, and nitrite in a bioreactor with efficient biomass retention.…”
Section: Background and Introductionmentioning
confidence: 99%
“…Ammonium was measured colorimetrically at 623 nm after a 30-min reaction of 100-μL samples with alkaline phenol catalyzed by sodium nitroprusside at 37°C (36). For the miniaturized setup (Exetainer incubations), nitrate was quantified with HPLC using a conductivity detector (26). Fe 2+ was measured using the ferrozine method (37).…”
Section: Methodsmentioning
confidence: 99%
“…Additions of 13 C-labelled CH 4 and analysis of lipid biomarkers indicated that CH 4 -derived C was incorporated into the biomass of both the bacterium and the archaeon, but to a lesser degree in the archaeon. It is not clear what is driving this pattern, but it is important to point out that the enrichment culture in this study utilized nitrite (NO Ettwig et al (2010Ettwig et al ( , 2008 showed that NO − 2 -driven AOM can occur in the absence of an Archaeal partner and is carried out by an anaerobic denitrifying bacterium that oxidizes CH 4 aerobically by reducing NO − 2 to N 2 and O 2 . This could explain why less of the labeled CH 4 -C was recovered from the archaeon.…”
Section: Non-peatland Ecosystemsmentioning
confidence: 99%
“…Panganiban et al, 1979;Smith et al, 1993;Eller et al, 2005), two landfills (Bjerg et al, 1995;Grossman et al, 2002), anoxic waste slurries (Malek and Weismann, 1988), a contaminated aquifer (Smith et al, 1991), and flooded-rice paddies (Miura et al, 1992;Murase and Kimura, 1994b), but much of the evidence is anecdotal in nature and strong evidence for AOM in freshwater systems has been limited. Work by Islas-Lima et al (2004) and Raghoebarsing et al (2006) has demonstrated that AOM in some freshwater systems is linked to denitrification and dentrifying bacteria, which provides an energetically favorable alternative to marine AOM linked to SR. Further work has suggested that AOM can be carried out by denitrifying bacteria in the absence of an archeal consortium (Ettwig et al, 2008) and that this process might be linked to nitrite (NO − 2 ) reduction and the production of oxygen (O 2 ) as an electron acceptor ; hence, implying aerobic metabolism under anoxic conditions.…”
Section: Introductionmentioning
confidence: 99%